Efektivitas Media Geogebra Terhadap Kemampuan Pemahaman Konsep Matematis Pada Materi Perbandingan Trigonometri Pada Segitiga Siku-siku - Rohim, Nur Muhammad; Achmad buchori (Universitas Muhammadiyah Kotabumi, 2024)
The purpose of this study is to determine how well educational materials based on geometry may improve students' comprehension of mathematical concepts within the context of trigonometric comparison involving right triangles at the high school level (Class X). The research employs a nonequivalent control group design, with participants comprising 34 at SMA N 14 Semarang, 36 pupils from Class X 3 and 36 students from Class X 2. Data collection encompasses interviews and assessments, with analysis conducted in two stages: initial data examination utilizing a pretest and final data scrutiny employing a posttest. Each stage involves assessments for normality, homogeneity, t-test, and N-Gain. The findings reveal that the utilization of the instructional media yielded a significant improvement in the experimental group, evidenced by an N-Gain score of 0.59 (59%), markedly higher than the control group's score of 0.30 (30%). In summary, the integration of Geogebra-based media in teaching trigonometric comparisons involving right triangles is demonstrated to be effective, fostering a positive impact on students' comprehension of mathematical concepts.